2008
DOI: 10.1007/s10517-009-0327-3
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Mitochondrial Potential as a Marker for Isolation of Pure Cardiomyoblast Population

Abstract: Typical signs of cardiomyoblasts were determined: high mitochondrial membrane potential and high number of mitochondria in these cells compared to fibroblasts. These signs can be used for identification of these cells. Energy-dependent accumulation of highly specific mitochondrial fluorescent probes applied for visual detection of energized mitochondria allows clear-cut separation of the mixed population: cardiomyocyte population is characterized by higher transmembrane potential than concomitant cells. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Terzic et al, have reported improved global cardiac function in iPS cell treated mice, however, without substantiating cardiogenesis in the infarcted mice heart with immunohistological evidence. 8 Given the tumorgenic nature of pluripotent stem cells, it is important to ensure that the transplantation of SiPS is free of undifferentiated cells 24 which are potential contributors of tumorgenicity of iPS cells 16 . Even the use of isogenic animals for transplantation of SiPS failed to curtail their teratogenic characteristics in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Terzic et al, have reported improved global cardiac function in iPS cell treated mice, however, without substantiating cardiogenesis in the infarcted mice heart with immunohistological evidence. 8 Given the tumorgenic nature of pluripotent stem cells, it is important to ensure that the transplantation of SiPS is free of undifferentiated cells 24 which are potential contributors of tumorgenicity of iPS cells 16 . Even the use of isogenic animals for transplantation of SiPS failed to curtail their teratogenic characteristics in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to neutropenia, the loss of TAZ function also causes cardiomyopathy in BTHS. In contrast to mature neutrophils that have very few mitochondria, both myeloid progenitor cells and cardiomyoblasts/cardiomyocytes depend heavily on mitochondria (49–52), which may explain why the loss of mitochondrial protein tafazzin has more severe effects on these specific tissues and results in neutropenia and cardiomyopathy in BTHS.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, in contrast to neutrophils with few if any mitochondria, human myeloid progenitor cells as well as cardiac cells depend heavily on mitochondria, which is why any abnormalities leading to mitochondrial dysfunction will have detrimental consequences for the normal function and survival of these cells leading to neutropenia and cardiomyopathy as opposed to other cells that are normal and do not depend on mitochondria (Fossati et al , ; Khryapenkova et al , ; van Raam et al , ; Kohlhaas et al , ; Makaryan et al , ). Similar to other neutropenic patients, G‐CSF treatment of BTHS patients increases the level of circulating neutrophils to near normal levels resulting in reduced frequency of infection episodes (Cox et al , ; Adwani et al , ).…”
Section: Cellular Models Of Bthsmentioning
confidence: 99%